Charging Station for Mobile Phone in Borobudur Village - Ikke Dian Oktaviani; Sidik Prabowo; Endro Ariyanto (JAPATUM: Jurnal Pemanfaatan Teknologi untuk Masyarakat, 2025)
Borobudur Village, known as one of the main tourist destinations in Indonesia, not only offers natural and cultural beauty, but also technological innovations aimed at improving visitor comfort. One of the latest initiatives is the technology transfer activity of making cellphone chargers provided for visitors. This activity aims to provide easy and affordable charging facilities for visitors who often need quick access to electricity while enjoying their tour. This technology is adopted to support the daily needs of visitors, especially those who rely on mobile devices for navigation, communication, and documentation while in the tourist area. The technology transfer process involves technical training for local communities to make and maintain charger devices, which not only increases their technical knowledge but also provides new economic opportunities. In addition, the introduction of this technology also supports the village's efforts to integrate modern services with the concept of sustainable tourism. With this cellphone charger facility, Borobudur Village is expected to increase its tourist appeal and provide a more comfortable experience for visitors, while strengthening the role of local communities in developing a tourism-based economy.